Bonegraft Wrap Technique: Avoiding Accentuated Labiomental Groove After Genioplasty - Kluppel, Leandro Eduardo; Trento, Guilherme [UNESP]; Claudino, Guilherme; Sebastiani, Aline Monise; Scariot, Rafaela (Lippincott Williams & Wilkins, 2019)
This work presents the wrap technique developed by the authors aiming to avoid the occurrence of unaesthetic deep labiomental fold in genioplasty. The technique recommends the use of particulate bone graft that is wrapped on collagen or a Surgicel membrane which is placed over the osteotomized segment of the chin fixated with a prebent 4-hole titanium plate.
Keywords: Esthetics; face; genioplasty; oral; surgery